Tolerance to Uncertainty and Superstition as Personal Resources for Solving Social Problems by Students - M.Y. Sachkova; L.E. Semyonova (Психолого-педагогические исследования)
The phenomena of tolerance/intolerance to uncertainty and belief in the paranormal as personal resources for solving social problems by students were examined. The relevance of the topic is due to an attempt to identify the necessary personal determinants that help to effectively cope with life difficulties in the face of the uncertainty and multitasking in the modern world. Hypotheses about the inverse correlation between tolerance to uncertainty and superstition, as well as the direct correlation between tolerance and a rational style and positive orientation, belief in the paranormal with a negative orientation, an avoidant and impulsive style of solving social problems have been put forward. The results of an empirical study conducted among university students studying at the social science, humanities and medical faculties are presented (N=252), aged 18 to 21 years. A set of diagnostic techniques was used: the questionnaire for solving social problems by M.M. Danina et al., the "Paranormal Belief Scale" by J. Tobacyk (adaptation by D.S. Grigoriev), the modified questionnaire of tolerance to uncertainty by S. Badner (adaptation by T.V. Kornilova, M.A. Chumakova). According to the results of the study, it was found that students have a low tendency towards superstition and more often use a rational style when solving social problems. They are also characterized by a predominantly positive problem orientation. The direct correlations of tolerance to uncertainty with a rational style and positive problem orientation, as well as negative connections with avoidant and impulsive styles, a negative problem orientation were found.